Indicadores de alfabetização científica como prática da transformação social e da dimensão socioemocional em livros didáticos de ciências da natureza: uma análise de atividades e conteúdo de ecologia - Santos, Geam Felipe Lima (2023)
In the last two decades of the 21st century, we have witnessed a series of issues related to environmental, political, and the COVID-19 health crisis, human rights violations, and the widespread circulation of misinformation. Faced with this, much thought has been given to the teaching of science/biology in this century, its role in the school curriculum and in society, especially in how it can contribute to a scientific education in which the individual understands themselves as a transformative agent in society. This research aims to analyze indicators of scientific literacy as a practice of social transformation and the socio-emotional dimension in activities related to ecological knowledge proposed in the 2021 PNLD (National Textbook Program) textbooks for Natural Sciences and their Technologies. The methodology adopted was based on Content Analysis from Bardin's perspective (2011), involving three stages: pre-analysis, analysis, and interpretation.It should be noted that our corpus of analysis was the collection approved by the PNLD 2021 for High School, specifically volumes 3 and 4 of "Moderna Plus: Natural Sciences and their Technologies." The data analysis is based on the theoretical perspective of Duschl (2008), Stroupe (2015), Silva and Sasseron (2021), Pizarro (2014), Oliveira (2019), which discuss the fundamental elements for implementing scientific literacy committed to social transformation. Also, Bento, Junior, and Rossi (2022) and their contributions to socio-emotional dimensions.Through the analytical procedure, it was identified that the indicators of the domains of scientific knowledge, scientific literacy committed to social transformation, and affective dimensions are not presented in the activities of the volumes and chapters in an integrated and balanced manner. This integration and balance are crucial requirements for achieving scientific literacy in our time, especially aligned with the challenges and issues of the 21st century.In light of the findings, it reveals the pressing need for an integrated and balanced mobilization of the domains of scientific knowledge because if they are worked on in isolation and disconnected, they contribute little or almost nothing to the kind of scientific literacy that shapes individuals as agents of transformation in their reality. This applies not only to the indicators of scientific literacy aimed at social transformation, especially those related to creating and acting, as they were rarely seen in the activities proposed in the analyzed textbooks but also to socio-emotional dimensions, which were rarely engaged and, in some chapters, did not appear in the proposed activities.The results indicate that the proposals of educational collections to meet the objectives of the New High School, in the context of the activities and contents of Ecology that we analyzed, contribute little to the process of scientific literacy that goes beyond conceptual and theoretical dimensions. It should also promote a process of transformation of the individual within society, specifically in collective civic action, a form of political, social, and cultural activism.